Experimental examination of effectiveness of vegetation as bio-filter of particulate matters in the urban environment. (January 2016) - Chen, Lixin; Liu, Chenming; Zou, Rui; Yang, Mao; Zhang, Zhiqiang
Abstract: Studies focused on pollutants deposition on vegetation surfaces or aerodynamics of vegetation space conflict in whether vegetation planting can effectively reduce airborne particulate matter (PM) pollution. To achieve a more comprehensive understanding of the conflict, we conducted experiments during 2013 and 2014 in Beijing, China to evaluate the importance of vegetation species, planting configurations and wind in influencing PM concentration at urban and street scales. Results showed that wind field prevailed over the purification function by vegetation at urban scale. All six examined planting configurations reduced total suspended particle along horizontal but not vertical direction. Shrubs and trees–grass configurations performed most effectively for horizontal PM2.5 reduction, but adversely for vertical attenuation. Trapping capacity of PMs was species-specific, but species selection criteria could hardly be generalized for practical use. Therefore, design of planting configuration is practically more effective than tree species selection in attenuating the ambient PM concentrations in urban settings. Highlights: Study of the relationship between vegetation and PM pollution is presented. Type of vegetation is secondary to wind field effect in influencing urban-scale PM pollution. Planting spaces aiding ventilation are crucial in roadside PM pollution control. Species differences are obvious but difficult to apply in practice. Abstract : Wind field triumphs surface deposition by vegetation in attenuating PM pollution, indicating consideration of ventilation as the criteria for spatial planting configuration and species selection.